2003
DOI: 10.1093/nar/gkg810
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and biochemical interactions between SCP160 and EAP1 in yeast

Abstract: Scp160p is a multiple KH-domain RNA-binding protein in yeast known to associate with polyribosomes as an mRNP component, although its biological role remains unclear. As a genetic approach to examine Scp160p function, we applied an ethyl methanesulfonate (EMS) screen for loci synthetically lethal with scp160 loss, and identified a single candidate gene, EAP1, whose protein product functions in translation as an eIF4E-binding protein, with additional uncharacterized spindle pole body functions. To reconfirm scp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 28 publications
0
37
0
Order By: Relevance
“…This role could be regulated by phosphorylation because Scp160 is phosphorylated upon inhibition of the TOR complex by rapamycin, mimicking amino acid starvation (Soulard et al, 2010). In addition, Scp160 is part of a complex that contains Eap1, a negative regulator of translation (Cosentino et al, 2000;Mendelsohn et al, 2003). In fact, the Smy2, Eap1, Scp160, Asc1 (SESA) complex has been shown to act as a translational repressor of the POM34 mRNA in response to spindle pole body (SPB) duplication defects (Sezen et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…This role could be regulated by phosphorylation because Scp160 is phosphorylated upon inhibition of the TOR complex by rapamycin, mimicking amino acid starvation (Soulard et al, 2010). In addition, Scp160 is part of a complex that contains Eap1, a negative regulator of translation (Cosentino et al, 2000;Mendelsohn et al, 2003). In fact, the Smy2, Eap1, Scp160, Asc1 (SESA) complex has been shown to act as a translational repressor of the POM34 mRNA in response to spindle pole body (SPB) duplication defects (Sezen et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…We found that in response to rapamycin treatment, isogenic wild-type and eap1⌬ cells both displayed a similar decrease in the P/M ratio (data not shown), which argues in fact against a major role of TORC1 in regulating translation initiation via Eap1p. Interestingly, however, Eap1p is predominantly associated with membranes and interacts genetically and biochemically with the ERassociated polyribosomal protein Scp160p (72). Moreover, it is known that Eap1p inhibits translation initiation following a membrane stress imposed by either application of the amphiphilic drug chlorpromazine or a block (in sec mutant cells) of the membrane transport to the plasma membrane (4,6).…”
Section: Discussionmentioning
confidence: 99%
“…We analyzed about 40 genes with roles in translation control, the UPR pathway (Sidrauski and Walter 1997), and nuclear envelope function (Supplemental Table 1) for their requirement in the viability of mps2D 2mm-SMY2 cells. This analysis identified the genes coding for the polysomeassociated, mRNA-binding protein Scp160 that has been shown to exist in a complex with Eap1 (Mendelsohn et al 2003), the Scp160-interacting protein Asc1 (essential for ER localization of Scp160) (Baum et al 2004), and the brefeldin A resistance protein Bfr1 (a component of polyribosome-associated mRNP complexes) (Lang et al 2001), as being essential in the mps2D 2mm-SMY2 background (Figs. 2E,F, 3A; Supplemental Table 1).…”
Section: Eap1 Allows Bypass Of Mps2 Function By Inhibiting Translatiomentioning
confidence: 99%